Crafting professionals: Skills and resources for graduates entering the craft economy. (December 2022) - England, Lauren
There is growing interest in creative graduate skillsets, but so far there has been limited investigation of the specific skills and resource requirements of early-career crafts graduates. Drawing on qualitative interviews and quantitative rankings of skills and resources conducted with 25 graduates from four higher education providers in England, this article examines the role and relative priority of different skills and resources in establishing a professional practice. It is identified that the skills and resources key to professional practice are highly interrelated, and proposed that the diverse requirements for professional practice should be understood as an amalgam rather than isolated components, with the acquisition of skills and resources seen as accumulative. The potential for a lack of key resources to exacerbate inequalities in who can enter and work in the craft economy is discussed and recommendations made for initiatives that could help to address an unequal distribution of resources.